The Role of Play in the Development of a Child's Personality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is devoted to the role of play in the formation of a child's personality. The features of the process of socialization of preschoolers are described, the influence of play activity on the formation of socially oriented personality traits is revealed, and the influence of the Internet space on the child is also considered.